2007
DOI: 10.1074/jbc.m609223200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Role of the Truncated βIV-Spectrin Σ6 in Sodium Channel Clustering at Axon Initial Segments and Nodes of Ranvier

Abstract: At axon initial segments and nodes of Ranvier in neurons, the spectrin membrane skeleton plays roles in physically stabilizing the plasma membrane integrity and in clustering voltage-gated sodium channels for proper conduction of the action potential. ␤IV-Spectrin, an essential component of the membrane skeleton at these sites, has an N-terminal-truncated isoform, ⌺6, which is expressed at much higher levels than the full-length isoform ⌺1. To investigate the role of ␤IV-spectrin ⌺6, we generated ⌺1-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…Moreover, while it is likely that each isoform has a unique role in heart (e.g., β IVΣ6 -spectrin localizes Na v channels to AISs in neurons, ref. 28), the specific functions of β IV -spectrin splice variants in heart remain unknown. Based on conservation of the CaMKII-and ankyrin-G-binding motifs in Σ1 and Σ6 isoforms, we anticipate that both isoforms will be important for regulation of Na v channel activity and cell excitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while it is likely that each isoform has a unique role in heart (e.g., β IVΣ6 -spectrin localizes Na v channels to AISs in neurons, ref. 28), the specific functions of β IV -spectrin splice variants in heart remain unknown. Based on conservation of the CaMKII-and ankyrin-G-binding motifs in Σ1 and Σ6 isoforms, we anticipate that both isoforms will be important for regulation of Na v channel activity and cell excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we identify β IV -spectrin, a key structural component required for ion channel clustering (including voltage-gated Na + channels) in the nervous system (27)(28)(29)(30)(31)(32)(33)(34), as a multifunctional regulatory stage for Na + channel signaling in excitable cells. β IV -spectrin targets critical structural and regulatory proteins to excitable membranes in heart and brain, and animal models harboring mutant β IV -spectrin alleles display aberrant cellular excitability and whole-animal physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Mutant mouse studies showed that ␤IV⌺6 plays a specific role in nodal Nav channel clustering, whereas ␤IV⌺1 stabilizes nodal membrane integrity (3,4,7). Mutant mice lacking ␤IV⌺1 present nodal shape alterations, which are very similar to those observed in ⌬10 mice (3,4). Some degree of nodal protrusion was also observed in qv 3J mice (5).…”
Section: Discussionmentioning
confidence: 86%
“…In mammalian cells, the mechanical support of the plasma membrane, as well as the microscale organization of membrane-spanning proteins, is provided by the association of spectrins and ankyrins, which promote the formation of an actin-based network coupled to the inner surface of the plasma membrane (30). Mutant mouse studies showed that ␤IV⌺6 plays a specific role in nodal Nav channel clustering, whereas ␤IV⌺1 stabilizes nodal membrane integrity (3,4,7). Mutant mice lacking ␤IV⌺1 present nodal shape alterations, which are very similar to those observed in ⌬10 mice (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation